Wastewater reuse - Radosavljević, Milan R.; Šušteršič, Vanja M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Water scarcity and water pollution are some of the crucial issues that must be addressed within local and global perspectives. One of the ways to reduce the impact of water scarcity and to minimizine water pollution is to expand water and wastewater reuse. The local conditions including regulations, institutions, financial mechanisms, availability of local technology and stakeholder participation have a great influence on the decisions for wastewater reuse. The increasing awareness of food safety and the influence of the countries which import food are influencing policy makers and agriculturists to improve the standards of wastewater reuse in agriculture. The environmental awareness of consumers has been putting pressure on the producers (industries) to opt for environmentally sound technologies including those which conserve water and reduce the level of pollution. It may be observed that we have to move forwards to implement strategies and plans for wastewater reuse. However, their success and sustainability will depend on political will, public awareness and active support from national and international agencies to create favorable environment for the promotion of environmentally sustainable technologies. Wastewater treatment has a long history, especially in agriculture, but also in industry and households. Poor quality of wastewater can pose a significant risk to the health of farmers and users of agricultural products. The World Health Organization (WHO) is working on a project for the reuse of wastewater in agriculture. To reduce effects of human activities to the minimum, it is necessary to provide such technical and technological solutions that would on the one hand ensure complying with the existing regulations and legislation, and on the other hand provide economically viable systems as seen through investments and operating costs. The use of wastewater The practice of using wastewater varies from country to country. Its application and technology applied are ​​significantly dependent on socio-economic circumstances, industry structure, climate and politics. Reuse of water for irrigation of agricultural crops Fourty-one percent of the recycled water in Japan, 60% in California (USA), and 15% in Tunisia is used for irrigation of crops. In China, at least 1.33 million hectares of agricultural land is irrigated with untreated or partially treated wastewater (http://www.eolss.net). Agricultural irrigation is essential to improve the quality and quantity of production. By 2025, agriculture is expected to increase its water requirements by 1.2 times (http://www.unep.or.jp). If wastewater originatines from industrial sources, the presence of toxic chemicals, salts and heavy metals may limit its reuse. Such materials can change soil properties and may affect the growth of crops, so that appropriate treatment and supervision should be practiced. Recycled water that is important for agriculture must contain nitrogen, potassium, zinc, boron and sulfur. However, excess nitrogen can lead to overgrowth, delayed crop maturity and poor quality. Boron is an essential element for plant growth, and the excess boron becomes toxic. Tunisia is one of a few countries that have implemented a national policy for the reuse of wastewater. Since 1960., the wastewater in Tunisia has been used for irrigation of orchards. Since 1989, after a secondary treatment, the wastewater has been used for the cultivation of various crops (olives, fodder, cotton, etc.), except for growing vegetables. In countries such as Morocco, Jordan, Egypt, Malta, Cyprus and Spain, wastewater is either used or being considered for irrigation, while in Israel, the percentage of the use of wastewater for irrigation is the highest in the region, with 24.4% and should be increased to 36% in the future (http://www.eolss.net). Depending on the country, socio-economic conditions, may be different, starting from the shortage of money for capital investments. Therefore, the EU funds are very important for the countries such as Greece anor Serbia. Egypt, Jordan, Tunisia, Palestine, Morocco and Syria irepresent a group of countries with a high need for the reuse of wastewater, but also with prevailing economic problems, limited experience, inadequate infrastructures, including sewers and wastewater treatment factories. Strict standards for the reuse of water such as the standards in California and other states in the U.S.A. (USEPA 1992),are not easy to achieve. The WHO directive is less severe, and it defines the treatment of wastewater for irrigation of crops, especially in developing countries. The countries that are the EU members, such as Greece, can expect to be provided with funding to improve health and to implement certain laws and regulations (Andreadakis A.. et al., 2001, 7th Conference on Environmental Science and Technology, Greece, September nd) Reuse of wastewater from households Gray water is water that comes from common household activities such as shaving, showering and washing machines. Since graywater represents 50-80% of common household water consumption, environmentalists believe that its discharge into drains is a waste and a missed opportunity to use such a resource. It can easily be captured, treated on site and reused in toilets and for landscaping, instead of commonly used drinking water. Systems used for purification and disinfection depend on countries and requirements that treated water must meet. In Australia, it is not allowed to treat water from the kitchen as gray water because of the presence of food, i.e. possible and therefore may be presen pathogenic organisms which make the purification process difficult. Some other states prohibit the reuse of gray water from washing machines- since cloth diapers can be washed in them clot, the water can be contaminated with faeces despite no contact with the main sewage drains. In California, treated gray water has been used for garden irrigation for years, and studies have shown that its use does not cause health problems. Reuse of gray water means less energy consumption and less chemicals in wastewater treatment plants, which is good for the community, i.e. households will be spending significantly less money on water bills. Reuse of wastewater from industry In industry, water is used in refrigeration, industrial process and power boilers. In the purification of industrial wastewater two approaches are generally distinguished: a pretreatment of wastewater that must be implemented to meet the criteria for its discharge into public sewers and a singular wastewater treatment (without interference from household waste) to meet the criteria for effluent to be discharged. More and more freguently companies release their waste into urban sewage,having previously partially refined it to the level where it is mixed with wastewater from households and then finally purified in the same installation. The composition of water for steam boilers is of very great importance, because the slightest disturbance in the steam boiler can cause a disturbance in the entire industrial process. The quality of water for steam boilers depends on the type of a plant, steam pressure and the purpose for which steam is used. Water should be of such quality that it does not leave residues and deposits and it should not have a corroding effect. The purity of produced steam should correspond to the purpose of the steam in question. Water should not contain substances that could cause foaming (fats, oils and other organic substances) and should be slightly alkaline (pH = 7 to 9.5). Industrial water, depending on the processes in the industry, can be purified up to a certain degree. When discharged into natural water systems, it must meet the principles underpinning the system of the limit values of major wastewater parameters, developed by The Association for wastewater from the Federal Republic of Germany and presented in Table 6. Conclusion The date presented here, including quantities, methods of treatment, use of treated wastewater and different regulations, lead to a conclusion that in order to reach the standards of developed countries, the Republic of Serbia needs experts and a long time period to treat its wastewater to an adequate level for its reuse as well as for the sparing use of its water sources in general.